Mercureid Gives New Opportunities for Treatment and Prevention of Complications Caused by COVID-19 in Patients with Ophthalmic Pathologies - Величко, Людмила Миколаївна; Богданова, Олександра Вікторівна; Храменко, Наталія Іванівна; Коновалова, Наталія Валеріївна (My University, 2021)
The coming era of COVID-19 introduces critical challenges for researchers. Accordingly, new questions connected with the current state of people’s health arise, namely, what consequences will be for the patients who have suffered from long COVID-19; what diseases are supposed to threaten the patients in the future; what immunity responses will be after the influence of antigen SARS-CoV-2; to what extent the organism changes caused by SARS-CoV-2 contribute to or prevent from the development of long-term protective immunity; how effective COVID19 vaccine will be for these patients. In this connection, some of the above-mentioned items have been highlighted in this research work. The study was conducted in 49 patients with ophthalmic pathologies who had previously undergone COVID-19. It should be stressed that examination of eye disorders is very essential because they allow in a non-traumatic way to obtain lifetime visualization of the state of blood vessels and capillaries, as well as to assess the effect of the virus on the central nervous system. Moreover, immunological studies made it possible to draw a conclusion about the state of antiviral immunity, immune status and its correlation with the severity of inflammatory processes in the eye structure, the central nervous system including the vascular endothelium. The novelty of the study is in establishing a causal relationship between SARS-CoV-2 infecting and formed dysfunction of immune parameters that caused the manifestation of chronic inflammatory diseases. As a result, light adaptation was impaired by 2.3 times, due to the damage to blood circulation owing to the neurotoxic effect of SARS-CoV-2 and hypoxemia. The corrective effect of drug Mercureid was registered in 73.4% of patients. It should be indicated that the most serious cases were observed in the group of patients with the damage to the retinal vascular system: the phenomenon of re-thrombosis of both the central retinal vein and its branches, as well as circulatory disorders in the optic nerve trunk - ischemic optic neuropathy with a sharp deterioration in vision. In these patients, the combination of vascular drugs and drug Mercureid allowed stabilizing the patients’ state, achieving remission and in 50.0% of cases having higher visual functions. Firstly, Mercureid made venotonic and angioprotective effect. It reduced vein elasticity and capillary permeability. Moreover, it improved venous outflow and microcirculation that allowed in some cases to restore lymphatic drainage. According to the results of the immune study, the targeted effect of the new drug Mercureid, aimed at modulating the activity of several critical target proteins, such as CD3, CD4, CD8, CD25, CD38, CD54, CD95 was revealed. The therapeutic efficacy of Mercureid was 75.1%. The second research finding is that in patients with manifestation of chronic inflammatory diseases who have previously been infected with SARS-CoV-2, the production of specific protective antibodies is supposed to be impaired (as these patients often have pathologically low levels of CD4, CD8, CD25 and overexpression of CD38, ICAM-1, CD95 that, consequently, causes apoptosis of immune cells, lymphopenia and also forms the phenotype of exhausted T-cells with activation of the expression of inhibitory receptors). Thus, we consider vaccination to be ineffective for them, due to the presence of a compromised immune system. Accordingly, the provision of corrective multitarget immunotherapy aimed at several target proteins, which are critical for the formation of long-term effective post-viral immunity to SARS-CoV-2, is certainly an important therapeutic need. This immunotherapy can be carried out both before and after vaccination in order to achieve the maximum protective effect from the vaccine. However, the definite answer to this research question requires another type of study design, which is under our further consideration.
Keywords: Immunotherapy; SARS-Cov-2; COVID-19; Ophthalmology